177k views
3 votes
−6(2x+8)= -6(2x+8)
How would you solve an equation like this?

1 Answer

4 votes

Answer:

Infinite Solutions

Explanation:

Since the two equations are set equal to each other, and are exactly equal they are always infinite solutions

PROOF:

- For example, we will say X = 1

-6 (2[1] + 8) = -6(2[1] + 8)

-6 (2+8) = -6 (2+8)

-6 (10) = -6 (10)

-60 = -60

For example, we will say X = 2

-6 (2[2] + 8) = -6(2[2] + 8)

-6 (4+8) = -6(4+8)

-6 (12) = -6 (12)

-72 = -72

Hope this helps! :)

User TwP
by
6.0k points